Optimizing Bioelectricity Production from Thermophilic Bioelectrogens Consortium Using Agricultural Waste in Microbial Fuel Cells - Apriansa, Apriansa; Irdawati, Irdawati (Jurnal Biologi Tropis, 2025)
Significant economic and population growth around the world has led to various problems, especially fossil fuel scarcity, energy production, as well as an increase in the volume of organic waste (agricultural, municipal, and industrial waste). As an alternative energy source, Microbial Fuel Cell (MFC) was chosen due to its promising prospects. The use of thermophilic bacteria and consortiums were chosen for their potential advantages in MFC systems. This study aims to explore the potential of thermophilic bioelectrogenous bacterial isolates of Sungai Sapan Aro (SSA) consortium 14&16 in producing bioenergy using various agricultural waste substrates (corn cob, rice straw, rice husk, and glucose as control). The results showed no significant difference in the use of agricultural waste substrates in the MFC system. Quantitatively, corn cobs produced voltages almost equivalent to glucose (control), while rice straw and rice husk produced lower voltages. The resulting voltages were glucose (0.59467 V), corn cob (0.57633 V), rice straw (0.43300 V), and rice husk (0.40400 V). The results of this study show better performance compared to previous studies in the field of electricity generation through MFCs.